Ketamine-Assisted Psychotherapy for Treatment- Resistant Depression with Comorbid Post-Traumatic Stress Disorder in Veterans - Oleh Orlov; Viacheslav Zaika; Oleh Fitkalo (Insight: the psychological dimensions of society, 2025)
The aim of the study was to evaluate the practice of using ketamine-assisted psychotherapy (KAT) in accordance with international clinical guidelines at the State Institution “Center for Mental Health and Veterans’ Rehabilitation ‘Lisova Polyana’ of the Ministry of Health of Ukraine” (Ukraine). Adapting the international clinical guidelines on ketamine therapy for treatment- resistant depression within the Ukrainian medical system in the context of war was the main focus of the study. Methods. The study had an open- label, non-blinded naturalistic design with a single group of participants (n = 27). The sample included veterans with confirmed treatment- resistant depression (TRD) and PTSD symptoms. The KAT course consisted of 1–4 ketamine infusions at doses of 0.5–1.0 mg/kg of body weight, accompanied by preparatory and integration psychotherapy sessions. Symptom dynamics were assessed using the “PHQ-9” (Kroenke et al., 2001), “BDI” (Beck et al., 1996), and “PCL-M” (Weathers et al., 1993) questionnaires. Psychodiagnostics were performed before treatment, after treatment, and one month after treatment. Nonparametric statistical methods (Wilcoxon signed-rank test, Spearman’s correlation coefficient, Hedges’ g) and correlational analysis were applied to explore relationships between outcomes and other variables. Results. The majority of participants demonstrated a significant reduction in depression symptoms (PHQ-9: p < .001, g = 1.31; BDI: p < .001, g = 1.20) and PTSD symptoms (PCL-M: p < .001, g = 1.10). More than 50.00% of participants achieved either substantial clinical improvement or remission. In 22.00–26.00% of participants, symptoms remained unchanged or slightly worsened, underscoring the need for an individualized treatment approach. The positive therapeutic effect persisted for at least one month after completion of treatment. While no correlation was found between KAT outcomes and participants’ age or the therapist’s personality, baseline symptom severity moderately correlated with effect size. Conclusions. The findings indicate high effectiveness of KAT as an innovative approach for treating resistant mental disorders in veterans. Combining pharmacological and psychotherapeutic components demonstrates significant potential for integration into Ukraine’s mental health system. However, the results require confirmation in larger samples and controlled experimental studies. The proposed therapeutic model could serve as a foundation for improving national clinical guidelines for the treatment of PTSD and depression among veterans.